ANALYSIS OF STUDENTS' ABILITY TO IDENTIFY SYMBOLIC REPRESENTATIONS IN CHEMISTRY - Martini Martini (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
To describe the behavior of matter and energy, chemists classify them in three distinct domains: macroscopic, microscopic, and symbolic. The ability to use these three representations is the basis for understanding concepts in chemistry. This study aims to analyze students' ability to identify symbolic representations in chemistry. The research design uses a one shot case study. The subjects of this study were students of prospective science teachers as many as 85 students. Data collection techniques using tests and rubrics. The results showed that of the ten symbolic representation statements, only three statements achieved the highest percentage of correct answers, namely statements about writing ionization reactions and writing electron symbols. There are two statements where almost 90 percent of students answered incorrectly. The statement is about reversible or irreversible reaction equations and exothermic reaction equations. From this research, it can be concluded that students' ability to identify symbolic representations in chemistry still needs to be improved, because the average score is still low.